Genetic parameters of productive and reproductive traits in Cinta Senese pig [Tuscany] - Crovetti, A. (Florence Univ. (Italy). Dipartimento di Scienze Zootecniche); Bozzi, R. (Florence Univ. (Italy). Dipartimento di Scienze Zootecniche); Pugliese, A. (Florence Univ. (Italy). Dipartimento di Scienze Zootecniche); Acciaioli, A. (Florence Univ. (Italy). Dipartimento di Scienze Zootecniche); Franci, O. (Florence Univ. (Italy). Dipartimento di Scienze Zootecniche) (Italian journal of animal science, 2005)
[The study was aimed at highlight if it is possible to improve some productive and reproductive traits of Cinta Senese breed. From 1999 to 2004, farrowings in three important farms of Cinta Senese were registered, number of born alive and weaned piglets per litter and related genetic parameters (heritability, maternal effect, inbreeding coefficient of sow and litter) were estimated. Data on IMG, lean and fat cut percentage, ham percentage of 111 subjects were also taken into account, estimating heritability and inbreeding effect. The results indicate that a improvement of reproductive traits is possible through a careful mating planning aimed at reducing inbreeding, while selection may be feasible for productive traits.] L´indagine è volta a evidenziare se esista o meno la possibilità di migliorare alcune caratteristiche produttive e riproduttive della razza Cinta Senese. Sono stati registrati i parti dal 1999 al 2004 in tre allevamenti "nucleo", è stata calcolata la media del numero di nati vivi e il numero di svezzati per parto e i relativi parametri genetici (ereditabilità, effetto materno, effetto della consanguineità, sia della madre, sia dei nati). Sono stati inoltre presi in considerazione l´IMG, la percentuale di tagli magri, di tagli grassi e del prosciutto su 111 soggetti, stimandone l´ereditabilità e l´effetto che la consanguineità ha su di essi. I risultati indicano che un miglioramento dei caratteri riproduttivi è possibile solo attraverso un´attenta pianificazione degli accoppiamenti volta a ridurre la consanguineità, mentre per i caratteri produttivi sembrerebbe percorribile anche la strada del miglioramento genetico per via selettiva